Association of FKBP5 Polymorphisms With Suicidal Events in the Treatment of Resistant Depression in Adolescents (TORDIA) Study - Brent, David (2009)
OBJECTIVE: The authors sought to assess the relationship between candidate genes and two clinical outcomes, namely, symptomatic improvement and the occurrence of suicidal events, in a sample of treatment-resistant depressed adolescents. METHOD: A subsample of depressed adolescents participating in the Treatment of SSRI-Resistant Depression in Adolescents (TORDIA) trial, 155 of whom were of European origin, were genotyped with respect to 21 polymorphisms on 12 genes that have a reported association with depression, treatment response, or suicidal events. Participants had not responded to a previous adequate trial with an antidepressant and were randomized to receive either another selective serotonin reuptake inhibitor or venlafaxine, with or without cognitive-behavioral therapy (CBT). Single-nucleotide polymorphism (SNP) analyses were conducted using PLINK with permutation procedures. RESULTS: No relationship was observed between any polymorphism and response to treatment. The FKBP5 (which codes for a protein causing subsensitivity of the glucocorticoid receptor) rs1360780TT and rs3800373GG genotypes were associated with suicidal events (N=18), even after controlling for treatment effects and relevant covariates. These two SNPs were in significant linkage disequilibrium (r=0.91). CONCLUSIONS: The FKBP5 genotypes associated with suicidal events in this study have been reported by others to cause the greatest degree of glucocorticoid receptor subsensitivity. These results are consistent with those of other studies linking alterations in the hypothalamic-pituitary-adrenal axis with suicidal behavior. The small number of events and lack of a placebo condition make these results preliminary. Replication with a larger sample and a placebo condition is needed to assess whether these events are related to treatment.